2010
DOI: 10.1177/0731684410391512
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of MWNT-reinforced thermoplastic natural rubber nanocomposites

Abstract: This article studies the thermal properties of a multi-walled carbon nanotube (MWNT)-reinforced thermoplastic natural rubber (TPNR) nanocomposite. The nanocomposite was prepared using a melt blending method. Various percentages (1, 3, 5, and 7 wt%) of MWNTs were added into TPNR to improve its thermal properties. The laser flash technique was also employed to determine the thermal conductivity, thermal diffusivity, and specific heat capacity of the nanocomposite. The DMA result showed that the glass transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…As a result of this unique arrangement, it not only display an improvement in mechanical response of the material, but also other properties such as gas barrier, fire resistance, thermal, and electrical conductivities. CNTs have been widely used with different kinds of polymers to obtain beneficial mechanical and physical properties for recent years . The results showed that CNTs could effectively improve elastic modulus, stress at a defined elongation, abrasion resistance and electrical properties compared to the CB additive.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this unique arrangement, it not only display an improvement in mechanical response of the material, but also other properties such as gas barrier, fire resistance, thermal, and electrical conductivities. CNTs have been widely used with different kinds of polymers to obtain beneficial mechanical and physical properties for recent years . The results showed that CNTs could effectively improve elastic modulus, stress at a defined elongation, abrasion resistance and electrical properties compared to the CB additive.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8C and D reveals the interfacial interactions, dispersion and adhesion of the MWCNTs within the matrix, representating pulled nanotubes (highlighted by white arrows) in HNC2. Strong interfacial adhesion is a key factor for establishing efficient heat transfer inside the matrix (TPNR); this fact is supported by the observation that the greater heat transfer efficiency of the MWCNTs enhanced the thermal properties of TPNR [35,38].…”
Section: Morphological Examinationmentioning
confidence: 99%
“…Many previous studies have focused on the dispersion of CNTs and the TR, which were regarded as the major factors affecting the thermal conductivity of CNT/polymer composites . Several approaches have been studied in order to improve the dispersion of CNTs in polymer matrix, such as addition of surfactants as well as various physical methods, such as high‐power ultrasonic stirring and rapid mechanical mixing with high strength . Although these methods can improve the dispersion of CNTs in polymer matrix without decreasing the thermal conductivity of CNTs, they cannot improve the weak interfacial interaction (Van der Waals' force) between CNTs and polymer matrix, which limits phonon transfer in CNT/polymer composites.…”
Section: Introductionmentioning
confidence: 99%